Analisa Besarnya Kontribusi Biaya Tak Langsung Terhadap Harga Jual Rumah Pada Perumahan Jenis Cluster Tipe 45 Di Kota Pekanbaru (Studi Kasus : Perumahan Mini Cluster Nirwana Cipta) - Iriana, Rian Trikomara (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The growth of property business in Pekanbaru creates a good economic growth. In 2011, this sector gives 27,72% income and improve the house demand indirectly. People ask for a good, healthy, safe, and well organized housing for midle people. Mini cluster is one of the choice for the housing, since this type of house combine a simple house with cluster concept, fully equipped with infrastructure facility and a full utility. There are two main fund in building a housing; direct and indirect costs. Direct costs is costs that we need for buiding the physic of the house, while the other costs is costs that we need for facility costs, legal permission costs, planning and economic costs. Indirect costs will be paid by buyers. So, the price paid by the buyers include facility building, legal permission, planning, and economic costs. In this research, writer has identified that the contribution of indirect costs give a big impact in house price and the profit. In percentage, the contribution of indirect costs is bigger than the profit. We can see that from 45/112 type house has 65, 75% for direct costs, 19% indirect costs, and 15, 25% for the profit. While for 45/143 type house, the percentage is 64, 13% for direct costs, 20, 19% for indirect costs, and 15, 68% for the profit. Facilities offered in mini cluster Nirwana Cipta housing are neighborhood street, closed drainage, small park in every unit, street lamp, and gate (one gate system).Key words : direct costs, indirect costs, selling price house, mini cluster.